2013
DOI: 10.1111/jns5.12022
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of a multimerized immunoglobulin Fc in an animal model of inflammatory neuropathy (experimental autoimmune neuritis)

Abstract: Intravenous immunoglobulin (IVIg) is one of the first-line therapies for inflammatory neuropathies. Clinical use of IVIg for these disorders is limited by expense and availability. Here, we investigated a synthetic product alternative to IVIg. The aim of this study was to test the therapeutic efficacy of a novel recombinant polyvalent murine IgG2a Fc compound (stradomer™) in experimental autoimmune neuritis (EAN). Seventy-four Lewis rats were immunized with myelin, randomized into three groups, and were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Our findings in the IVIg-treated mice are consistent with an earlier study [33] which showed that IVIg can suppress disease in the rat model of EAMG. In addition, these results add to previously published studies in which fully recombinant IgG2a Fc multimers have been shown to alleviate collagen-induced arthritis in a dose-dependent fashion, to prevent idiopathic thrombocytopenic purpura in mice [25], and to ameliorate clinical, electrophysiologic, and histologic disease in experimental autoimmune neuritis (EAN) [34]. Interestingly, we noted a rapid decline in the clinical score shortly after each treatment with M045 and IVIG.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings in the IVIg-treated mice are consistent with an earlier study [33] which showed that IVIg can suppress disease in the rat model of EAMG. In addition, these results add to previously published studies in which fully recombinant IgG2a Fc multimers have been shown to alleviate collagen-induced arthritis in a dose-dependent fashion, to prevent idiopathic thrombocytopenic purpura in mice [25], and to ameliorate clinical, electrophysiologic, and histologic disease in experimental autoimmune neuritis (EAN) [34]. Interestingly, we noted a rapid decline in the clinical score shortly after each treatment with M045 and IVIG.…”
Section: Discussionsupporting
confidence: 80%
“…M-045 avidly binds all murine Fcγ receptors (FcγRs) and mediates protection against platelet loss in a model of immune thrombocytopenic purpura (ITP), and therapeutic efficacy in a murine collagen-induced arthritis (CIA) model. Importantly, different scientific teams recapitulated the validity of these findings in models of myasthenia gravis and experimental autoimmune neuritis (27,28).…”
Section: Introductionmentioning
confidence: 81%
“…The murine immunoglobulin G2a (IgG2a)-based version of this drug, M-045, was effective in the prevention and/ or treatment of a variety of rodent models of autoimmunity, including immune thrombocytopenic purpura, collagen-induced arthritis, 12 myasthenia gravis, 13 and experimental autoimmune neuritis. 14 Similarly, GL-2045 was effective in animal models of immune thrombocytopenic purpura and collagen-induced arthritis (X.Z. and J.O., manuscript submitted April 2016).…”
Section: Introductionmentioning
confidence: 99%